Doom loop, trilemma, and moral hazard: Which narrative of the banking union did stock market investors buy? - Tobias Körner; Michael Papageorgiou (Deutsche Bundesbank, 2024)
We analyze the impact of the announcement of the banking union on stock market returns of euro area banks against the backdrop of three commonly held views of the banking union. We document positive individual abnormal returns for most banks. Abnormal returns are large and positive on average, and they vary substantially across banks. The more systemically important a bank is, the higher are the abnormal returns, both in 'crisis countries' and 'non-crisis countries'. Moreover, abnormal returns of banks are positively related to sovereign risk, with Greek banks experiencing extremely high abnormal returns. By contrast, abnormal returns are not robustly related to bank risk. These findings reveal market expectations consistent with the view that the banking union makes banks less dependent on their home country's sovereign strength and mitigates a financial trilemma. However, market participants do not seem to take the view that the banking union reduces a moral hazard problem that may emerge from a common lender of last resort and national responsibilities for banking supervision and resolution.
Keywords: G01; G21; G28; 330; Euro area crisis; banking union; sovereign-bank nexus; systemic risk; event study